Nursing home adjustment in China: mediating and moderating effects - Binbin Yong; Yanyan Zhang; Huimin Xiao (BMC Geriatrics, 2023)
Abstract Purpose Adjusting to nursing homes contributes to successful aging in older adults. However, the effect of stress on psychological adjustment in nursing home residents is unclear. Therefore, this study aimed to explore the relationship between stress and psychological adjustment among nursing home residents. Methods This was a cross-sectional, multicenter survey. A total of 386 residents from 11 nursing homes were included in the study. Bootstrapping with resampling strategies was used to examine multiple mediators and the moderator effect. This research conforms with the STROBE checklist. Results Path analysis demonstrated that stress directly negatively predicted the psychological adjustment of nursing home residents. It also indirectly predicted psychological adjustment through the mediating role of learned resourcefulness and self-efficacy, as well as the chain mediating role of both. Social support played a moderating role in the path of stress to learned resourcefulness. Conclusion This study revealed the mechanism underlying the effect of stress on psychological adjustment in nursing home residents without cognitive impairment and walking difficulties. It further suggests that health providers could enhance older adults' learned resourcefulness, self-efficacy, and social support to assist them in adjusting to nursing home life.